Prefácio e Organização - Muchaluat Saade, Débora C.; Barbosa, Jorge Luis Victória (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2024: Proceedings of the 30th Brazilian Symposium on Multimedia and the Web, 2024)
Este documento traz o Prefácio e a Organização dos Anais do WebMedia 2024.